Interpreting political participation as communicative action: a comparison of younger and older adults - Déri, András; Szabó, Andrea (Frontiers in Political Science, 2025)
IntroductionThis study investigates the subjective interpretations of political participation among different age groups, focusing on youth and older adults. Building on an interpretivist approach, the research challenges prevalent assumptions about engagement patterns.MethodsData were collected through a representative Hungarian survey (N = 2,972). Respondents assessed various political acts in terms of whether they considered them to be political participation. The sample was divided into two age cohorts: 18–29 and 60+ years.ResultsThe results reveal significant differences between age groups: while younger respondents are more likely to associate institutional forms with participation, older individuals display greater recognition of online engagement and conversational activities as legitimate forms of political involvement. Regression models highlight that older men are particularly inclined to view digital activism as political participation.DiscussionThese findings challenge stereotypes of online participation as a youth-dominated phenomenon and underscore the evolving roles of digital platforms in shaping political agency across age cohorts. By integrating theoretical and empirical insights, the study emphasizes the importance of subjective meaning-making in conceptualizing participation. It advocates for a reevaluation of established frameworks, arguing that top–down typologies may inadequately reflect diverse, context-dependent understandings. The findings hold broader implications for refining participatory research methodologies and fostering inclusive mobilization strategies.